2002
DOI: 10.1200/jco.2002.02.090
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Trial of Oral TAC-101, a Novel Retinoic Acid Receptor-Alpha Selective Retinoid, in Patients With Advanced Cancer

Abstract: This is the first human clinical study with TAC-101, a RAR-alpha selective retinoid. Musculoskeletal toxicity and hypertriglyceridemia were observed characteristics of previously studied retinoids. The recommended phase II dose is 24 mg/m(2) with this treatment schedule. Alternative treatment schedules and prospective evaluation of thrombotic risk will be investigated in subsequent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…RAR-specific retinoids are being developed and evaluated in the hope of improved specificity and a reduced side effect profile over conventional pan-RAR agonists. 12,58 The identification of pathways specific for the distinct RARs, such as Mad1 and p27 Kip1 for RAR␣-mediated cell cycle arrest pathways, may allow a more rational application of these compounds. Our study also reveals that RAR␥-induced differentiation of granulocyte progenitors occurs independent of Mad1 and p27 Kip1 status, highlighting potential differences in target genes among the RARs that may be able to be therapeutically exploited.…”
Section: Discussionmentioning
confidence: 99%
“…RAR-specific retinoids are being developed and evaluated in the hope of improved specificity and a reduced side effect profile over conventional pan-RAR agonists. 12,58 The identification of pathways specific for the distinct RARs, such as Mad1 and p27 Kip1 for RAR␣-mediated cell cycle arrest pathways, may allow a more rational application of these compounds. Our study also reveals that RAR␥-induced differentiation of granulocyte progenitors occurs independent of Mad1 and p27 Kip1 status, highlighting potential differences in target genes among the RARs that may be able to be therapeutically exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Through its binding to RAR , TAC-101 interferes with the binding of AP-1 to DNA, and inhibits production of urokinase plasminogen activator (uPA) and matrix metalloproteinase 9 (MMP-9). In several studies, TAC-101 has shown inhibition of tumor growth and hepatic metastases in several cancers including colorectal, gastric, pancreatic, and lung cancer and inhibits angiogenesis via down regulation of vascular endothelial growth factor (VEGF) mRNA and protein in a colon cancer model (Hashimoto et al 1996;Murakami et al 1998a, b;Oikawa 1998;Fujimoto et al 1999;Miyaguchi et al 2001;Oikawa et al 2001;Rizvi et al 2002;Lee et al 2003;Miyagawa et al 2003;Sano et al 2003;Satake et al 2003;Yoshimura et al 2003;Minagawa et al 2004;Shudo et al 2004;Suzuki et al 2004;Sako et al 2005). In a gastric cancer animal model, TAC-101 was shown to decrease cellinduced angiogenesis (decreased microvessel density and new blood vessel formation).…”
Section: Discussionmentioning
confidence: 96%
“…The initial doseescalation study of TAC-101 in patients with advanced cancer showed a similar toxicity proWle. (Rizvi et al 2002) Retinoids are capable of inhibiting growth and inducing diVerentiation in tumor models, including HCC (Yasuda et al 2002;Matsushima-Nishiwaki et al 2003). In clinical studies, retinoids have demonstrated potential beneWt in both the prevention and treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the toxic effects of TAC-101 were consistent with those of previous studies. (7,8) Higginbotham et al reported the results of pharmacokinetic studies of TAC-101 in patients with advanced hepatocellular carcinoma treated in the United States. (8) The mean pharmacokinetic parameters (t max , 4.3 h; C max , 242 ng/mL; AUC 0-24 , 3067.6 ng h/mL; AUC inf , 4241.1 ng h/mL) obtained for a dose of 20 mg were generally consistent with our data in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
“…VTE developed in nine of 29 patients as a characteristic adverse reaction of TAC-101; the dose ranged from 12 to 34 mg/m 2 . (7) In a phase I/II study, TAC-101 was administered orally in 21-day cycles (14 days on/7 days off) to patients with advanced HCC. In the phase I portion of the study, the initial dose was 40 mg/day.…”
mentioning
confidence: 99%